Natural Enemies of Soft Scale insects (Hemiptera: Coccidae) on Orchard Trees in Syrian southern and coastal region (Damascus University Journal of agriculture sciences, 2021)
Natural enemies of some soft scale insects which infest orchard trees (almonds, figs, olive, and citrus) were studied between 2015 – 2017. The following soft scale insects: European fruit lecanium Parthenolecanium corni (Bouché) on almonds in Damascus Countryside and Quneitra, black scale, Saissetia oleae (Olivier) on olive, fig wax scale (FWS) Ceroplastes rusci L. on fig trees in Quneitra, Citricola Scale, Coccus pseudomagnoliarum (Kuwana) and brown soft scale, Coccus hesperidum (Linnaeus) (Hemiptera: Coccidae) on citrus trees, in Lattakia, were recorded. The predators:  Chilocorus bipustulatus L., Exochomus quadripustulatus L., Rhyzobius lophanthae (Blaisdell), Nephus redtenbacheri (Mulsant), Pharoscymnus sp., Nephus quadrimaculatus (Herbst), Nephus bipunctatus (Kugelann), Scymnus coniferarum (Crotch), Scymnus abietis (Paykull), Scymnus rubromaculatus (Goeze) and Scymnus sp. (Coleoptera: Coccinellidae), Eublemma scitula (Rambur) and Calymma communimacula (Denis and Schiffermüller) (Lepidoptera: Noctuidae) Chrysoperla carnea (Stephens) and Dichochrysa astur (Banks) (Neuroptera: Chrysopidae), Hemerobius humulinus (Linnaeus) )Neuroptera: Hemeropiidae), The following parasitoids were determined with: Chalcidoidea: Encyrtidae: Metaphycus helvolus (Compere), M. lounsburyi )Howard(, M. insidiosus (Mercet), Blastothrix longipennis )Howard(, Discodes coccophagus (Ratzeburg), Anagyrus kamali (Moursi), Cheiloneurus claviger (Thomson), Cerapterocerus mirabilis (Westwood), Encyrtus sp., Encyrtus aurantii (Geoffroy), Homalotylus flaminius  (Dalman), Homalotylus sp., Metaphycus flavus (Schlupfwespe), and Microterys nietneri (Motschulsky). Aphelinidae: Coccophagus lycimnia (Walker), C. semicircularis (Förster), Ablerus sp., Marietta picta (André), and Coccobius fulvus (Compere and Annecke).  Eriaporidae:  Promuscidea unfasciativentris (Girault). Eulophidae: Tetrastichus sp., Elasmus platyedrae (Ferrière) and Aprostocetus ceroplastae (Girault). Pteromalidae: Scutellista nigra (Mercet), S. caerulea (Fonscolombe) and Pachyneuron muscarum (Linnaeus). In addition, the parasitic mite, Pyemotes tritici (Lagreze-Fossat and Montane), (Acari: Trombidiformes), was found attacking larvae of C. communimacula inside the soft scale Parthenolecanium corni.
Keywords: Fig; Almond; Olive; Citrus